1997
DOI: 10.1097/00005392-199706000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Horseshoe Kidney is Associated With an Increased Relative Risk of Primary Renal Carcinoid Tumor

Abstract: The relative risk of renal carcinoid tumor developing in a horseshoe kidney is markedly greater than that for Wilms tumor or transitional cell carcinoma. The clinical course of renal carcinoid tumor arising within a horseshoe kidney appears to be more benign than that of the nonhorseshoe variant. Our observations support the hypothesis that renal carcinoid tumors may arise from neuroendocrine cells within foci of metaplastic or teratomatous epithelium within the kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 0 publications
2
58
1
2
Order By: Relevance
“…Of these, 11 were found in association with HSK. Krishnan [4] estimated that the relative risk for NET developing in a HSK is 62, which is greater than that reported for Wilms tumor and transitional cell carcinoma of the renal pelvis. Adding recent cases reported, Motta [1] suggested that the relative risk rises to 120.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Of these, 11 were found in association with HSK. Krishnan [4] estimated that the relative risk for NET developing in a HSK is 62, which is greater than that reported for Wilms tumor and transitional cell carcinoma of the renal pelvis. Adding recent cases reported, Motta [1] suggested that the relative risk rises to 120.…”
Section: Discussionmentioning
confidence: 79%
“…Hematuria and pyuria may be present [1]. Carcinoid syndrome is rarely associated with primary renal carcinoid tumor, even in case of metastatic disease [1,4,7]. The classical Carcinoid syndrome occurs in less than 10% of patients with gastrointestinal carcinoid and in less than 5% of patients with pulmonary carcinoid [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 A review of the English literature revealed only 38 cases of renal carcinoid tumors reported in the world. Krishnan et al 3 reviewed 32 cases of this tumor in 1997. After their report six further reported cases 4-9 could be found.…”
Section: Introductionmentioning
confidence: 99%
“…The patient was discharged uneventfully, and remains in good health without any evidence of disease recurrence at 24 months after the operation. 3 reported an association of horseshoe kidney and the development of renal carcinoid. Because no APUD cells have been demonstrated in the normal kidney, 10 they hypothesized a possible relationship between metaplasitc or teratomatous epithelium within the horseshoe kidney and the development of the renal carcinoid.…”
Section: Introductionmentioning
confidence: 99%